Effect of antibiotics on polymorphonuclear leukocyte functions and myeloperoxidase activity, glutathione and malondialdehyde levels in allergic asthma - RAYAMAN, ERKAN; RAYAMAN, PERVİN; SOYOĞUL GÜRER, ÜMRAN (My University, 2015)
We investigated the effect of ciprofloxacin, rifampicine and doxycycline on myeloperoxidase (MPO) activity, glutathione (GSH) and malondialdehyde (MDA) levels in allergic asthma patients and healthy volunteers. Polymorphonuclear leukocytes (PMNs) were isolated with ficoll-hypaque gradient centrifugation method. MPO activity was assayed with modified o-dianisidine, GSH by Ellman's and MDA levels by Beuge's method. PMN functions and MDA levels of patients significantly decreased when compared with healthy volunteers. Ciprofloxacin significantly increased PMN functions, MPO activity and MDA levels of both groups. We have demonstrated that ciprofloxacin has beneficial effects on MPO activity and PMN functions in allergic asthma patients and healthy volunteers.